A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations - Richardson, Steven; Trimm, Travis; Paredes, Randell; Koehl, Jonathan; Song, Hojun (Zootaxa, 2019)
A new king cricket species Glaphyrosoma stephanosoltis sp. nov. (Orthoptera: Anostostomatidae: Glaphyrosomatini) from mid-elevation tropical rainforests of Costa Rica is described. This new species represents the southernmost distribution of the genus Glaphyrosoma Brunner von Wattenwyl, 1888, which is widely distributed throughout Mexico, Guatemala, and Honduras. Biology of the new species is briefly described.